Effects of Microgravity on Early Embryonic Development and Embryonic Stem Cell Differentiation: Phenotypic Characterization and Potential Mechanisms - Li, Feng; Ye, Ying; Lei, Xiaohua; Zhang, Wensheng (Frontiers in Cell and Developmental Biology, 2021)
With the development of science and technology, mankind’s exploration of outer space has increased tremendously. Settling in outer space or on other planets could help solve the Earth’s resource crisis, but such settlement will first face the problem of reproduction. There are considerable differences between outer space and the Earth’s environment, with the effects of gravity being one of the most significant. Studying the possible effects and underlying mechanisms of microgravity on embryonic stem cell (ESC) differentiation and embryonic development could help provide solutions to healthy living and reproduction in deep space. This article summarizes recent research progress on the effects of microgravity on ESCs and early embryonic development and proposes hypotheses regarding the potential mechanisms. In addition, we discuss the controversies and key questions in the field and indicate directions for future research.